2022
DOI: 10.1177/10888683221107267
|View full text |Cite
|
Sign up to set email alerts
|

Do Salient Social Norms Moderate Mortality Salience Effects? A (Challenging) Meta-Analysis of Terror Management Studies

Abstract: Terror management theory postulates that mortality salience (MS) increases the motivation to defend one’s cultural worldviews. How that motivation is expressed may depend on the social norm that is momentarily salient. Meta-analyses were conducted on studies that manipulated MS and social norm salience. Results based on 64 effect sizes for the hypothesized interaction between MS and norm salience revealed a small-to-medium effect of g = 0.34, 95% confidence interval [0.26, 0.41]. Bias-adjustment techniques sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 166 publications
0
11
1
Order By: Relevance
“…These attention- and engagement-check systems are, of course, not perfect, but have been found to detect most poor response quality in previous work [ 90 , 92 ]. Given established effects of researcher [ 30 , 35 ] and experimental style [e.g., 54 ], it may be that this specific method does not work in this context. Indeed, many, but not all, of the recent failures to replicate using this method have used online or crowd sourced samples [e.g., 47 , 49 , 50 ].…”
Section: Study 6: Summing Up Studies 1–5 Via Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…These attention- and engagement-check systems are, of course, not perfect, but have been found to detect most poor response quality in previous work [ 90 , 92 ]. Given established effects of researcher [ 30 , 35 ] and experimental style [e.g., 54 ], it may be that this specific method does not work in this context. Indeed, many, but not all, of the recent failures to replicate using this method have used online or crowd sourced samples [e.g., 47 , 49 , 50 ].…”
Section: Study 6: Summing Up Studies 1–5 Via Meta-analysismentioning
confidence: 99%
“…When using age as a moderator, the impacts of MS attenuated and even reversed (e.g., greater levels of egalitarian attitudes emerged) in samples of older adults [e.g., 28 , 29 ]. In a more recent meta-analysis, Schindler et al [ 30 ] identified a smaller, but significant overall pooled Hedge’s g of 0.34, or approximately r = .168. Schindler and colleagues focused on methods more than individual differences, the latter of which are discussed further below.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations